A new hybrid sorbent 2, 2'-pyridil functionalized SBA-15 (Pyl-SBA-15) synthesis and its applications in solid phase extraction of Cu(II) from water samples. Issue 3 (June 2019) - Imran, K.; Harinath, Y.; Ramesh Naik, B.; Sathish Kumar, N.; Seshaiah, K.
Graphical abstract: A mesoporous hybridmaterial, 2, 2-Pyridil-SBA-15(Pyl-SBA-15) was synthesized by anchoring 2, 2-Pyridil onto the surface of SBA-15. The application of Pyl-SBA-15 as a sorbent was applied in the separation and preconcentration of Cu(II) ions in water samples. Effect of different parameters like pH, volume of eluent, sample ﬂow rate and interfering ions was investigated. The preconcentration capacity value of the prepared material under optimized conditions for Cu(II) was 0.88 ± 0.01mmol g −1 . The Cu(II) ions collected onto the sorbent were eluted out with 6 mL of 1 M HNO3 and determined by atomic absorption spectroscopy (AAS). The enrichment factor and detection limit of Cu(II) were found to be 66.6 and0.38 μg/L respectively. Abstract: A mesoporous hybrid material, 2, 2 ' -Pyridil-SBA-15 (Pyl-SBA-15) was synthesized by anchoring 2, 2 ' -Pyridil onto the surface of SBA-15. The application of Pyl-SBA-15 as a sorbent in separation and preconcentration of Cu(II) ions in water samples was studied. Effect of different parameters like pH, volume of eluent, sample ﬂow rate and interfering ions was investigated. The preconcentration capacity value of the prepared material under optimized conditions for Cu(II) was 0.88 ± 0.01 mmol g −1 . The Cu(II) ions collected onto the sorbent were eluted out with 6 mL of 1 M HNO3 and determined by atomic absorption spectroscopy (AAS). The enrichment factor and detection limit of Cu(II) were found to be 66.6 and 0.38 μg L -1 respectively.